Bahasa Inggris - Abdurrahman Afiq Yuda Hammaami; Nain Dhaniarti Raharjo; Lalu Muhamad Jaelani (Institut Teknologi Sepuluh Nopember, 2026)
The Suramadu Bridge is a vital infrastructure connecting Java and Madura Islands. Pylons, as key components of cable-stayed bridges, are susceptible to geometric changes due to sea wave exposure, wind loads, and increasing traffic volume. This study analyzes the geometric displacement of pylons by comparing two periods of UAV LiDAR point cloud data acquired on 5 January 2026 and 2 February 2026 against the Detailed Engineering Design (DED). Data acquisition was conducted using a DJI Matrice 350 UAV with a Geosun GS-260H LiDAR sensor. The geometric analysis encompasses six dimensional parameters and pylon tilt calculated from the combined centroid of both pylon legs. Accuracy validation using ICP points based on SNI 9135-2:2023 confirmed both periods achieved Class 2 accuracy at 1:2,500 scale. The upper width parameter (L1) recorded the largest deviation of 186 mm on the Madura pylon in Period 3, while the middle thickness (T2) was identified as the most critical parameter due to consistently negative deviation, reaching 134 mm on the Madura pylon in Period 5. The Mean Absolute Error indicated that the MDR pylon (51 mm) exhibited greater dimensional change intensity than the SBY pylon (36 mm). Tilt analysis showed both pylons inclined convergently toward the main span, attributed to cable tension.